50 years after 1975 - Tanomkiat, Wiwatana (The ASEAN Journal of Radiology, 2025)
Fifty years after political turmoil in 1975, people in Southeast Asian countries are still struggling to live better lives. This issue reminds readers what happened to the people after the failure of the states’ administrations. In the post-colonial era, the ambiguous borders between continental ASEAN countries have periodically been adopted in a diversionary politics, often flaring into disputes over territory ownership and leading to significant casualties and displacements among local communities living near the border. The conflicts often prevent people from reaching the health care and education system.